2009
DOI: 10.1080/07418820802266462
|View full text |Cite
|
Sign up to set email alerts
|

Racial Bias in Case Processing: Does Victim Race Affect Police Clearance of Violent Crime Incidents?

Abstract: Prior studies have illustrated racial differences in perceptions of police legitimacy. African-Americans' views, however, appear to be complex, shaped by perceptions of over-enforcement of crimes committed by African-American offenders coupled with under-enforcement of crimes involving African-American victims. Using data from the 2002 National Incident-Based Reporting System, we examine whether victim race (alone, and in combination with offender race) affects police case clearance of four types of violent cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 66 publications
(94 reference statements)
2
40
1
Order By: Relevance
“…Using NIBRS data from 2000, Stolzenberg and D'Alessio (2004) report that arrest is less likely in stranger kidnappings. This relationship has also been observed in studies examining homicide, rape, robbery, simple assault, and aggravated assault (Addington, 2006;Eitle, Stolzenberg, & D'Alessio, 2005;Lee, 2005;Regoeczi, Jarvis, & Riedel, 2008;Roberts, 2008;Taylor, Holleran, & Topalli, 2009). Therefore, we predict the following:…”
Section: Arrestmentioning
confidence: 57%
“…Using NIBRS data from 2000, Stolzenberg and D'Alessio (2004) report that arrest is less likely in stranger kidnappings. This relationship has also been observed in studies examining homicide, rape, robbery, simple assault, and aggravated assault (Addington, 2006;Eitle, Stolzenberg, & D'Alessio, 2005;Lee, 2005;Regoeczi, Jarvis, & Riedel, 2008;Roberts, 2008;Taylor, Holleran, & Topalli, 2009). Therefore, we predict the following:…”
Section: Arrestmentioning
confidence: 57%
“…Therefore, offense clearance rates represent a fundamental metric for evaluating police performance (Braga & Dusseault, 2008; Cook, ). Researchers have attributed variation in clearance rates to an array of factors, including victim–offender relationships (Dugan, Nagin, & Rosenfeld, ; Ousey & Lee, ), victim–offender characteristics (e.g., race, class, gender, and age; Braga, Turchan, & Barao, ; Lee, ; Roberts, ; Taylor, Holleran, & Topalli, ), investigative tactics (Braga & Dusseault, ; Carter & Carter, ; Gilbert, ; Jang, Hoover, & Lawton, ; Wellford & Cronin, ; Wellford et al., ), evidence processing (Baskin & Sommers, ; McEwen, ; Schroeder & White, ), community context (Borg & Parker, ; Ousey & Lee, ; Regoeczi & Jarvis, ; Roberts, ), and lack of citizen cooperation (Jarvis & Regoeczi, ; Regoeczi & Jarvis, ). Scholars have consistently shown that cooperating witnesses substantially increase the likelihood of cases being cleared (Baskin & Sommers, ; Peterson, Sommers, Baskin, & Johnson, ; Wellford et al., ), especially eyewitnesses (Regoeczi & Jarvis, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…White victims broadly experience higher rates of arrest (Avakame et al 1999:778;Smith et al 1984). Cases with a white victim and white offender have the highest clearance rate of all victim-offender race combinations, with a 16 percent higher clearance rate than similar cases with a white victim and black offender (Taylor et al 2009). Generally, black victims experience less protection from the law, when compared to white victims (Smith 1984;Smith et al 1984).…”
Section: Arrestmentioning
confidence: 99%